Effect of Background Luminance Level on the Assessment of Color Visual Acuity Using Colored Landolt Rings in Young Healthy Subjects. (4th March 2018) - Tanaka, Yoshiki; Yokoyama, Sho; Horai, Rie; Kojima, Takashi; Hiroyuki, Sato; Kato, Yukihito; Takagi, Mari; Nakamura, Hideki; Tanaka, Kiyoshi; Ichikawa, Kazuo; Tanabe, Shoko
ABSTRACT: Purpose : To evaluate the color visual acuity (CVA) of young healthy subjects using colored Landolt rings and the effect of background luminance level on the CVA. Materials and methods : We measured the CVA of 20 young healthy subjects (age: 23.8 ± 3.8 years) with different colors using a computer and a liquid crystal display, with 15 Landolt ring colors (30 cd/m 2 ) with a background luminance of 30 cd/m 2, and then 100 cd/m 2 . We then used different background luminance levels (15–50 cd/m 2 ) using four Landolt ring colors (red, green–yellow, green, and blue–green) to evaluate the effect of the background luminance level on CVA. Results : The CVA significantly differed among the colors with a background luminance of 30 cd/m 2 ( p  < 0.0001). Green–yellow and blue–purple had poor CVA (high LogMAR value; 0.808 ± 0.107 and 0.633 ± 0.150, respectively) with a background luminance of 30 cd/m 2 (same luminance as the Landolt rings). There were no significant differences in the CVAs among the colors with a background luminance of 100 cd/m 2 ( p  = 0.5999). There were no significant difference in the CVA between background luminance 30 cd/m 2 and other luminance level ranging from 28 to 32 cd/m 2 for colors of red, green–yellow, green, and blue–green. Conclusions : The results reveal that the background luminance of Landolt rings affects the CVA. Distinctive CVAs for each color are measured by equalizing the luminance between the Landolt ring and the background. We consider that the poor CVAs of these colors reflect the visual function of S-cone, because GY and BP are included in the confusion locus of tritan axis on the chromaticity diagram. We believe that CVA assessment may be useful for individuals who have known or suspected ocular dysfunction or color vision deficiencies.